ANALYSIS OF THE INFLUENCE OF TECHNOLOGY AND LENGTH OF BUSINESS ON INCOME THROUGH LABOR AS AN INTERVENING VARIABLE IN MSMES COFFEE SHOPS IN MEDAN CITY - Nadia Adhani; Raina Linda Sari; Arif Rahman (Jurnal Apresiasi Ekonomi, 2026)
This research aims to analyze the influence of technology and business duration on the income of micro, small, and medium enterprises (MSMEs) coffee shops in Medan City, with labor as an intervening variable. The rapid growth of the coffee shop industry in Medan has intensified competition among business owners, making the adoption of technology, business experience, and labor effectiveness crucial factors for increasing income. This study employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The research sample consists of MSME coffee shop owners selected through purposive sampling. The variables include technology (X1), Length of a business (X2), labor (Z), and income (Y). The findings reveal that technology has a positive and significant effect on income and also influences labor. Business duration positively affects both income and labor. Moreover, labor significantly affects income and mediates the relationship between technology and income, as well as between business duration and income. These results indicate that optimal technology utilization, longer business experience, and sufficient labor quality are key determinants of income improvement among MSME coffee shops in Medan City. This research is expected to serve as a reference for business owners and policymakers in formulating strategies for sustainable MSME development.